Spatial working memory ability in individuals at ultra high risk for psychosis. - Goghari, V; Brett, C; Tabraham, P; Johns, L; Valmaggia, L; Broome, M; Woolley, J; Bramon, E; Howes, O; Byrne, M; McGuire, P (2014)
The goal of this investigation was to clarify the nature of spatial working memory difficulties in individuals at ultra high risk (UHR) for psychosis. We evaluated spatial working memory and intelligence in 96 individuals at UHR for psychosis, 28 patients with first episode psychosis (FEP), and 23 healthy controls. Fourteen UHR individuals developed a psychotic disorder during follow-up. Compared to controls, the UHR group was impaired in both the short-term maintenance of material and in the effective use of strategy, but not more immediate memory. These impairments were not as severe as those in the FEP group, as the UHR group performed better than the FEP group. A similar pattern of results was found for the intelligence measures. Discriminant function analyses demonstrated short-term maintenance of material significantly differentiated the UHR and healthy control groups even when accounting for full scale intelligence quotient (IQ); whereas full scale IQ significantly differentiated the UHR and FEP groups and FEP and control groups. Notably, within the UHR group, impaired spatial working memory performance was associated with lower global functioning, but not full scale IQ. The subgroup of UHR individuals who later developed psychosis was not significantly more impaired on any aspect of working memory performance than the group of UHR individuals who did not develop psychosis. Given, the relationship between spatial working memory deficits and functional outcome, these results indicate that cognitive remediation could be useful in individuals at UHR for psychosis to potentially improve functioning.